Avaliação da dor através de parâmetros subjetivos e marcadores salivares em pacientes durante tratamento ortodôntico com braquetes convencionais e autoligados - Silva, José Alberto da (2017)
Orthodontic treatment may be associated with unfavorable side effects such as discomfort and pain. One of the factors affecting tooth movement is the degree of friction between the arch and the bracket. Objective: The objective of this study was to evaluate and compare the concentrations of biological pain markers (Amylase, IgA and total Proteins) and salivary flow rate in patients treated with conventional and self-ligating brackets, as well as subjectively evaluating patients' pain After installation of the device through Visual Analogue Scale. Material and methods: 40 patients (17 male and 23 female) aged 8 to 16 years undergoing orthodontic treatment with conventional brackets (Group 1 n = 20) received twin brackets Kirium series 3M Abzil® (Ribeirão Preto, Brazil), and (Group 2 n = 20) received self-ligating brackets Portia 3M Abzil® (Ribeirão Preto, Brazil). The subjective analysis of pain and discomfort was performed using the visual analogue scale (VAS). The saliva samples were collected in the following four times: before the bonding of the brackets (T0), 24 h after (T1), 72 h after (T2) 1 week after (T3). Patients were instructed to complete VAS every day after appliance installation. A Mann-Whitney-Wilcoxon test was performed at a significance level of 5%, the groups did not present statistical differences. Results: we observed increased salivary flow rate for groups 1 and 2, decreased protein concentration in groups 1 and 2, decreased salivary amylase in group 1 and a slight increase in group 2 concentration, as well as a decrease in IgA concentration for groups 1 and 2 Conclusion: The patients presented pain and discomfort of medium intensity in the first 24 hours, decreasing in the other days until presenting absence of pain; There were no significant changes in salivary biomarkers, denoting that orthodontic treatment does not alter salivary dynamics in the buccal environment; There was no difference in the type of bracket used.